PRESSURE ULCERS IN PEDIATRIC PATIENTS: CAUSAL FACTORS AND THERAPEUTIC MANAGEMENT - Ramos, Gabriely Westphal; Monteiro, Daiane da Rosa; Rodrigues, Pâmela de Oliveira; Wegner, Wiliam; Breigeiron, Márcia Koja (Cogitare Enfermagem, 2023)
Objective: to trace the sociodemographic and clinical profile, causal factors, and therapeutic management provided to children with pressure ulcers during hospitalization. Method: cross-sectional study; retrospective. Sample of 64 medical records of children with PU, admitted to a hospital in southern Brazil, from January/2016 to July/2021. Data analyzed by descriptive and inferential statistics. Results: Profile of children in intensive care (62.5%); stage 1 pressure ulcers (35.9%); and use of simple cover (37.5%). Of the total cases, 25% by medical device use. Consultations were related to stage 3 injury (p=0.027). Nursing diagnosis risk of pressure ulcer was identified in 48.4% of cases, while the Braden/Braden Q scale was identified in 78.1%. Patients classified as high risk (46%) had limited mobility (p=0.000). Conclusions: Pressure ulcers in children in intensive care with limited mobility require everything from simple intervention to consulting according to the classification of the injury.